Optimization of dry sliding wear behavior of flyash & zirconia reinforced Al-Mg-1Si-Cu HMMC using Taguchi technique. (2020) - Fakkir Mohamed, M.; Yaknesh, S.; Radhakrishnan, G.; Mohankumar, P.
Abstract: This research represents an efficient conceptualization to improve the tribo characteristics of hybrid aluminium matrix composites (6061-Flyash-Zirconia) fictitious by stir casting method, with multiple performances supported by Taguchi Technique. During this study flyash was unbroken constant at 100% (6061, 6061–10% Flyash-2% Zirconia and 6061–10% Flyash-4% Zirconia) and Zirconia was varied from 0 to 4%. Dry sliding wear checks were conducted employing a well-planned experimental schedule supported by Taguchi's orthogonal arrays. The input parameters like Load (L), sliding Speed (S), sliding Distance (D) and Reinforcement (R) are optimized with issues of multiple performance characteristics: Specific Wear Rate (SWR) and Co-efficient of Friction (COF). The optimum levels of input parameters were selected from response table &graph. SEM was done to look at the worn surface of composite specimen. The regression equation was developed and valid through confirmative experiment.